Textbook of Ilizarov Surgical Techniques: Bone Correction and Lengthening - H Frankel Victor, Golyakhovsky Vladimir; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2010)
In this book Textbook of Ilizarov Surgical Techniques: Bone Correction and Lengthening include the recent developments, together with the new illustrations, and write some new chapters: (i) Gavriil Abramovich Ilizarov$1 (BThe Man, The Creator, The Teacher, (ii) Biomechanics of the Ilizarov external fixator, (iii) Ilizarov frame assemblage, (iv) Biomechanics of the Ilizarov method, (v) Biomechanic considerations for the fracture treatment, (vi) Basics of the method of distraction osteogenesis, (vii) Basics of the method of compression osteogenesis, and (viii) Criteria of bone healing and fixator removal. These chapters, composed together, have a purpose to serve as an introduction for the description of the Ilizarov techniques and methods. Some of these materials were scattered in the chapters of (3z(BOperative manual(3y (Bbut the author considers expedient for the reader to get to know these particular subjects before learning how to assemble and use the fixator. The last chapter of the book (3z(BThe New Modifications of the Ilizarov Technique(3y (Breflects the development of new innovations which were developed since circulation of the original Ilizarov$1 (Bs ideas in orthopedic community around the world. The apparent simplicity and clarity of the Ilizarov technique provoked many orthopedic surgeons to offer their own modifications, as it always happened to the great inventions. Some of the new modifications are based on advanced technology of new materials for fixator parts, there are introductions of aluminum rings, and carbon rings, and titanium rods. Some modifications consist of small technical innovations. All these modifications are governed by the principles discovered and technique developed by Dr. Ilizarov. The most essential innovation of the Ilizarov treatment is an addition of the computer programming to the calculation of bone deformity correction. The computer assisting control helps doctors and the patients to produce precalculated bone reduction, correction, compression and lengthening. Several special software programs including Internet-based programs are available in the US, Germany and other countries. But, as Professor Ilizarov was fond of saying: (3z(BTo perform the treatment properly and successfully, one must know the method as well as the apparatus.(3ys
Keywords: Orthopedics; Electronic books